Identification of Students Misconception Using Two-Tier Diagnostic Test Completed with Certainty of Response Index (CRI) on Topic Partial Salt Hydrolysis - Tomas Istantyo Putro; Sri Retno Dwi Ariani; Sri Yamtinah (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
This study’s aim was to find misconception pattern on partial salt hydrolysis on eleventh grade student science major at SMA Negeri 2 Sukoharjo. Misconception was identified using two-tier diagnostic test completed with CRI supported by observation on learning process also interview. Two-tier diagnostic test composed of 16 questions. The approach of this study was qualitative description which was held in February-June 2018. The subject of this study were the eleventh grade students class IPA 1 and IPA 4 as many as 72 students. According to the result showed that there was misconception on almost every concept’s part. Based on the student answer analysis result shows if the pH, relative atomic mass, and volume were known student were having biggest misconception on counting salt’s mass are, 75%. The reason of misconception that occurs on partial salt hydrolysis is come from the student it self that is student’s uncomplete reasoning pattern.